KEMAMPUAN PEMAHAMAN MATEMATIS MELALUI MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, DAN EXTENDING - Anizar, Anizar; Sofyan, Sofyan (Jurnal Math-UMB.EDU, 2016)
This research is a classroom action research with design several cycles which aims to know the improvement of the student ability on the mathematical understanding that using CORE type of cooperative learning. The research subjects were the seventh graders at SMP Muhammadiyah Integrated of Bengkulu City. the Instrument used in this research is a test sheet. As for the conclusion of this result research is, through the application of CORE type learning on the subject of waking flat trapezoidal at the seventh graders at SMP Muhammadiyah Integrated of Bengkulu City, the students’ mathematical understanding of each indicator has reached a predetermined success criterion, incluiding: the first cycle in a number of indicators that are in both categories are still not reaching the success criteria specified but at the second cycle of the entire indicators of the ability of mathematical understanding already be in either categories and the ability of mathematical understanding has achieved success criteria specified.